2022
DOI: 10.3390/v14051065
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of an Automated System for Assaying Anti-Hepatitis E Virus Immunoglobulins M and G Compared with a Conventional Microplate Assay

Abstract: To evaluate the diagnostic performance of the Liaison® Murex anti-HEV IgM and IgG assays running on the Liaison® instrument and compare the results with those obtained with Wantai HEV assays. We tested samples collected in immunocompetent and immunocompromised patients during the acute (HEV RNA positive, anti-HEV IgM positive) and the post-viremic phase (HEV RNA negative, anti-HEV IgM positive) of infections. The specificity was assessed by testing HEV RNA negative/anti-HEV IgG-IgM negative samples. The clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A total of 8 of the 17 samples found to be reactive by the recom Well HEV IgM ELISA were concordantly negative by the recom Line HEV IgM blot and by the DiaSorin and WANTAI IgM assays ( Table 3 ). Recently, good agreement was reported between HEV antibody tests from the latter two manufacturers [ 10 ]. The indices of samples No.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A total of 8 of the 17 samples found to be reactive by the recom Well HEV IgM ELISA were concordantly negative by the recom Line HEV IgM blot and by the DiaSorin and WANTAI IgM assays ( Table 3 ). Recently, good agreement was reported between HEV antibody tests from the latter two manufacturers [ 10 ]. The indices of samples No.…”
Section: Discussionmentioning
confidence: 95%
“…The sera were retested with the fully automated chemiluminescence immunoassays (CLIAs) LIAISON ® MUREX Anti-HEV IgG (DiaSorin Italia S.p.A., Saluggia, Italy; quantitative; positive ≥ 0.3 IU/mL) and LIAISON ® MUREX Anti-HEV IgM (qualitative; index ≥ 1.00), which use the gt 1 and 3 capsid proteins as antigens [ 10 ]. Available data from some patients with acute infection by HEV gt 1, 2 and 4 show that these tests can reliably detect the corresponding antibodies [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, only one study has previously evaluated these new assays to date. Recently, Abravanel et al [ 31 ] reported that the Liaison ® Murex assays are very sensitive and specific in comparison to the Wantai HEV assays, observing a rate of sensitivity of 100% for IgM and IgG assays with acute-phase samples from immunocompetent patients, although less for IgM (93.8%) and IgG (84.3%) assays obtained from immunocompromised patients. In addition, a sensitivity of 94.6% was observed for anti-HEV IgG and 57.4% for anti-HEV IgM using post-viremic samples from immunocompetent patients, which in turn was 93.5% and 71% for immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-HEV ELISA IgG has a linearity range of 1 IU/mL to 22 IU/mL with a detection limit of 0.1 IU/mL. Considering the variations in sensitivity among diverse commercial diagnostic kits for detecting HEV antibodies [13], the diagnostic assay was chosen based on specificity instead of sensitivity. The Euroimmun was selected based on its established high specificity of 100% for anti-HEV IgM and 99.3% for anti-HEV IgG in patients lacking markers of HEV infection, as observed in our study population [14].…”
Section: Serological Testingmentioning
confidence: 99%